Analyzing Innovation Drivers in the German Laser Industry: the Role of Positioning in the Social and Geographical Space - Muhamed Kudic; Peter Bönisch; Iciar Dominguez Lacasa (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
Empirical and theoretical contributions provide strong evidence that firm-level performance outcomes in terms of innovativeness can either be determined by the firm's position in the social space (network effects) or by the firm's position in the geographical space (co-location effects). Even though we can observe quite recently first attempts in bringing together these traditionally distinct research streams (Whittington et al. 2009), research on interdependent network and geographical co-location effects is still rare. Consequently, we seek to answer the following research question: considering that the effects of social and geographic proximity on firm's innovativeness can be interdependent, what are the distinct and combined effects of firm's network and geographic position on firm-level innovation output? We analyze the innovative performance of German laser source manufacturers between 1995 and 2007. We use an official database on publicly funded R&D collaboration projects in order to construct yearly networks and analyze firm's network positions. Based on information on population entries and exits we calculate various types of geographical proximity measures between private sector and public research organizations (PRO). We use patent grants as dependent variable in order to measure firm-level innovation output. Empirical results provide evidence for distinct effect of network degree centrality. Distinct effect of firm's geographical colocation to laser-related public research organization promotes patenting activity. Results on combined network and co-location effects confirms partially the existence of interdependent proximity effects, even though a closer look at these effects reveals some ambiguous but quite interesting findings. – – Sowohl empirische als auch theoretische Studien deuten darauf hin, dass die Innovationsleistung von Unternehmen einerseits von deren Netzwerkposition (network effects) und andererseits von ihrer geographischen Lage (co-location effects) beeinflusst wird. Auch wenn bereits erste Anstrengungen hinsichtlich der Integration dieser traditionell getrennten Forschungsströmungen zu beobachten sind (Whittington et al. 2009), so bleibt festzustellen, dass die Innovationskonsequenzen interdependenter Positionierungseffekte noch immer weitestgehend unerforscht sind. Daher besteht das Ziel des vorliegenden Beitrages darin, die folgende Forschungsfrage zu beantworten. Welchen Einfluss haben individuelle sowie interdependente Effekte der geographischen Lage und der Netzwerkpositionierung auf den Innovationserfolg von Unternehmen? Zur Beantwortung dieser Fragestellung untersuchen wir die Gesamtheit aller deutschen Laserstrahlquellenhersteller zwischen 1995 und 2007. Zeitpunktgenaue Informationen zur Bildung und Auflösung von Kooperationen bilden die Grundlage zur Berechnung jährlicher Netzwerkstrukturmaße. Basierend auf zeitpunktgenauen Industriedynamikdaten sowie den entsprechenden Adressinformationen wurden geographische Distanzvektoren zwischen unterschiedlichen Akteuren berechnet. Als abhängige Variable zur Messung des Innovationserfolgs wurden Patenterteilungsdaten herangezogen. Die empirischen Ergebnisse zeigen, dass individuelle Netzwerkeffekte - gemessen an der Anzahl direkter F&E Kooperationen - einen positiven Einfluss auf die Innovationsleistung ausüben. Ferner kann gezeigt werden, dass individuelle Effekte der geographischen Nähe von Laserstrahlquellenherstellern zu öffentlichen Forschungseinrichtungen sowie Universitäten die Patentaktivität der Firmen positiv beeinflussen. Schließlich konnte die Existenz interdependenter, komplementärer Effekte der geographischen Lage und Netzwerkpositionierung nachgewiesen werden, die es jedoch aufgrund partiell ambivalenter Ergebnisse in Folgestudien vertiefend zu untersuchen gilt.
urn:nbn:de:101:1-201011242805
Keywords: O31; O32; L25; 330; Geographical co-location; network positioning; innovation output; Geographische Distanz; Netzwerkpositionierung; Innovationserfolg